Detection of distant metastatic disease by positron emission tomography with 18F-fluorodeoxyglucose (FDG-PET) at initial staging of cervical carcinoma. (March 2019) - Lin, Alexander; Ma, Sirui; Dehdashti, Farrokh; Markovina, Stephanie; Schwarz, Julie; Siegel, Barry; Powell, Matthew; Grigsby, Perry
Abstract : Objective: The detection of distant metastatic disease in cervical cancer patients at diagnosis is critical in accurate prognostication and directing treatment strategies. This study describes the frequency and sites of distant metastatic disease at diagnosis in patients with cervical cancer as detected by positron emission tomography with 18 F-fluorodeoxyglucose (FDG-PET). Methods: Patients with newly diagnosed cervical cancer underwent pre-treatment whole-body FDG-PET starting in 1997 at an academic institution. Patients with evidence of distant FDG-avid disease, defined as disease outside of typical sites of lymphatic spread, were included for analyses. Patients were not surgically staged, but biopsy to confirm metastatic disease was attempted at the discretion of the treating physicians. Overall survival was calculated using Kaplan-Meier analysis. Results: From 1997 to 2017, 72 (6.2%) of 1158 consecutively evaluated cervical cancer patients exhibited FDG-avid distant disease at diagnosis; 27 (38%) of these had biopsy confirmation of distant disease. Only 35 (49%) of FDG-detected metastases were clinically apparent. The sites of distant disease were lung (35%), multiple sites (25%), omentum (16.5%), bone (16.5%), and liver (7%). There were 12 (17%) patients with distant disease who did not display FDG-avid lymph nodes. Median overall survival among patients with distant FDG-avid disease was 7.0 months (95% CI 4.3 to 9.7). Patients with multiple sites of distant disease demonstrated the worst overall survival. Conclusions: Distant metastatic disease detected by FDG-PET is found in 6.2% of patients with cervical cancer at the time of initial diagnosis and the most common site of disease is the lung. Further prospective investigation is warranted to delineate best treatment practices for cervical cancer patients presenting with distant metastases.